Marius Victorinus' Commentary on Galatians introduction, translation, and notes - Cooper, Stephen Andrew, 1958-; Victorinus, Marius (Oxford ; New York : Oxford University Press, 2005)
Marius Victorinus, a professor of rhetoric in 14th century Rome, wrote the first Latin commentaries on the apostle Paul, whose letters have played a vital role in Western Christian thought. This text provides an English translation of Victorinus' commentary on Galatians, presenting the apostle's passion for the freedom of the gospel.
Includes bibliographical references (p. [370]-403) and indexes.
Description based on print version record.
Keywords: Bible. -- Commentaries -- History and criticism; Victorinus, Marius; Bible. -- Commentaries -- Early works to 1800.; Victorinus, Marius; Bible. -- Commentaires -- Histoire et critique; Bible. -- Commentaires -- Ouvrages avant 1800.; RELIGION -- Biblical Studies -- New Testament; RELIGION -- Biblical Studies -- Paul's Letters; Galaten (bijbelboek); Exegese; Vroege kerk; Electronic books; Bible. N.T. Galatians -- Commentaries -- Early works to; Bible. N.T. Galatians -- Commentaries -- History and criticism; Victorinus, Marius. In epistolam Pauli ad Galatas; Religion